Ten-Year All-Cause Death According to Completeness of Revascularization in Patients With Three-Vessel Disease or Left Main Coronary Artery Disease: Insights From the SYNTAX Extended Survival Study. Issue 2 (13th July 2021) - Takahashi, Kuniaki; Serruys, Patrick W.; Gao, Chao; Ono, Masafumi; Wang, Rutao; Thuijs, Daniel J.F.M.; Mack, Michael J.; Curzen, Nick; Mohr, Friedrich-Wilhelm; Davierwala, Piroze; Milojevic, Milan; Wykrzykowska, Joanna J.; et al.
Abstract : Background: Ten-year all-cause death according to incomplete (IR) versus complete revascularization (CR) has not been fully investigated in patients with 3-vessel disease and left main coronary artery disease undergoing percutaneous coronary intervention (PCI) versus coronary artery bypass grafting (CABG). Methods: The SYNTAX Extended Survival study (Synergy Between PCI With TAXUS and Cardiac Surgery: SYNTAX Extended Survival [SYNTAXES]) evaluated vital status up to 10 years in patients who were originally enrolled in the SYNTAX trial. In the present substudy, outcomes of the CABG CR group were compared with the CABG IR, PCI CR, and PCI IR groups. In addition, in the PCI cohort, the residual SYNTAX score (rSS) was used to quantify the extent of IR and to assess its association with fatal late outcome. The rSS of 0 suggests CR, whereas a rSS>0 identifies the degree of IR. Results: IR was more frequently observed in patients with PCI versus CABG (56.6% versus 36.8%) and more common in those with 3-vessel disease than left main coronary artery disease in both the PCI arm (58.5% versus 53.8%) and the CABG arm (42.8% versus 27.5%). Patients undergoing PCI with CR had no significant difference in 10-year all-cause death compared with those undergoing CABG (22.2% for PCI with CR versus 24.3% for CABG with IR versus 23.8% for CABG with CR). In contrast, those with PCI and IR had a significantly higher risk of all-cause death at 10 years compared with CABG and CR (33.5% versus 23.7%; adjusted hazard ratio, 1.48 [95% CI, 1.15–1.91]). When patients with PCI were stratified according to the rSS, those with a rSS⩽8 had no significant difference in all-cause death at 10 years as the other terciles (22.2% for rSS=0 versus 23.9% for rSS>0–4 versus 28.9% for rSS>4–8), whereas a rSS>8 had a significantly higher risk of 10-year all-cause death than those undergoing PCI with CR (50.1% versus 22.2%; adjusted hazard ratio, 3.40 [95% CI, 2.13–5.43]). Conclusions: IR is common after PCI, and the degree of incompleteness was associated with 10-year mortality. If it is unlikely that complete (or nearly complete; rSS<8) revascularization can be achieved with PCI in patients with 3-vessel disease, CABG should be considered. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT00114972. URL: https://www.clinicaltrials.gov ; Unique identifier: NCT03417050. Abstract : Supplemental Digital Content is available in the text.